Modeling of deformation processes in amorphous-crystalline polymers - Shardakov, Igor Nikolaevich; Golotina, Lyudmila Alexandrovna (Computational Continuum Mechanics, 2009)
The present paper deals with consideration of a wide class of amorphous-crystalline polymers in which amorphous and crystalline phases may coexist. Under specific thermomechanical conditions, the amorphous phase may change into the crystalline phase, and the glass transition may take place. Using previous approaches, we have constructed a new variant of constitutive equations for describing the relationship between the stress-strain state and the crystallization and glass transition processes. The developed variant can adequately describe the effects of forced highelasticity, freezing and unfreezing of the deformed state and some others. Numerical results presented for different uniform stress-strain states demonstrate the capabilities of the proposed constitutive equations.
Keywords: amorphous-crystalline polymer; constitutive equations; numerical experiment